EasyChain: an IoT-friendly blockchain for robust and energy-efficient authentication - Bapatla, Anand K.; Puthal, Deepak; Mohanty, Saraju P.; Yanambaka, Venkata P.; Kougianos, Elias (Frontiers in Blockchain, 2023)
The Internet of Everything (IoE) is a bigger picture that tries to fit the Internet of Things (IoT) that is widely deployed in smart applications. IoE brings people, data, processes, and things to form a network that is more connected and increases overall system intelligence. Further investigating the IoE can really mean creating a distributed network focusing on edge computing instead of relying on the cloud. Blockchain is one of the recent distributed network technologies which by structure and operations provide data integrity and security in trust-less P2P networks such as IoE. Blockchain can also remove the need for central entities which is the main hurdle for wide adoption of IoT in large networks. IoT "things" are resource constrained both in power and computation to adopt the conventional blockchain consensus algorithms that are power and compute-hungry. To solve that problem, this paper proposes EasyChain, a blockchain that is robust along with running on a lightweight authentication-based consensus protocol that is Proof-of-Authentication (PoAh). This blockchain based on lightweight consensus protocol replaces the power-hungry transaction and block validation steps and provides ease of usage in resource-constrained environments such as IoE. The proposed blockchain is designed using the language Python for easy understanding of the functions and increased ease of integration into IoE applications. The designed blockchain system is also deployed on a single-board computer to analyze its feasibility and scalability. The latency observed in the simulated and experimental evaluations is 148.89 ms which is very fast compared to the existing algorithms.